2012
DOI: 10.1002/bies.201200081
|View full text |Cite
|
Sign up to set email alerts
|

Brain estrogen signaling effects acute modulation of acoustic communication behaviors: A working hypothesis

Abstract: Summary Although estrogens are widely considered circulating ‘sex steroid hormones’ typically associated with female reproduction, recent evidence suggests that estrogens can act as local modulators of brain circuits in both males and females. Functional implications of this newly-characterized estrogen signaling system have begun to emerge. This essay summarizes evidence in support of the hypothesis that the rapid production of estrogens in brain circuits can drive acute changes in both the production and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 102 publications
(107 reference statements)
2
20
0
Order By: Relevance
“…Our results for the auditory midbrain parallel a number of studies from other taxa that describe an important role for estradiol in sensory processing of social signals and of audition (Arch and Narins, 2009;Caras, 2013;Earp and Maney, 2012;Maney, 2013;Maney et al, 2006Maney et al, , 2008Maney and Pinaud, 2011;Petrulis, 2013;Remage-Healey, 2012, 2014Sanford et al, 2010;Sisneros, 2009c;Tremere et al, 2009;Walpurger et al, 2004;Yovanof and Feng, 1983). In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results for the auditory midbrain parallel a number of studies from other taxa that describe an important role for estradiol in sensory processing of social signals and of audition (Arch and Narins, 2009;Caras, 2013;Earp and Maney, 2012;Maney, 2013;Maney et al, 2006Maney et al, , 2008Maney and Pinaud, 2011;Petrulis, 2013;Remage-Healey, 2012, 2014Sanford et al, 2010;Sisneros, 2009c;Tremere et al, 2009;Walpurger et al, 2004;Yovanof and Feng, 1983). In the túngara frog, a previous study showed that hCG, which stimulates production of gonadal steroids (Lynch et al, 2006;Wu et al, 2001), increases egr-1 expression in the laminar nucleus of the torus (Lynch and Wilczynski, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…There are also broad correspondences between egr-1 (also known as ZENK) expression and electrophysiological activity in songbirds: ZENK expression is selective for conspecific social signals (song) over tones only in the presence of estradiol in female white-throated sparrows (Zonotrichia albicolis) (Maney et al, 2006(Maney et al, , 2008Maney and Pinaud, 2011). Estradiol also enhances auditory encoding of song, sometimes through rapid effects of brain-derived estradiol (Krentzel and Remage-Healey, 2015;Remage-Healey, 2012, 2014RemageHealey et al, 2010;Tremere and Pinaud, 2011). In zebra finches, the impact of estradiol extends further to the song control system, as estradiol enhances the neural selectivity for the bird's own song (BOS) but not to conspecific songs and fadrozole injections reduce this selectivity (Remage-Healey and Joshi, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Although most studies of T and mating effort have examined long-term changes in baseline T, recent attention has been given to the dynamic changes in T and other steroid hormones on sexual behavior on smaller time scales that can induce rapid changes in behavior, particularly in response to dynamic social conditions (Cross and Roselli, 1999;Mangiamele and Thompson, 2012;Remage-Healey and Bass, 2010;Remage-Healey, 2012). In rodents, like other mammals, transient increases (henceforth "pulses") of T have been widely observed among males in response to encounters with females (Batty, 1978;Coquelin and Bronson, 1980;James et al, 2006;Macrides et al, 1975;Nyby, 2008;reviewed by Gleason et al, 2009), but the consequences of these T pulses are not well understood, and even less so regarding extra-pair mating in monogamous species.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this issue of BioEssays, RemageHealey describes an elegant body of work demonstrating that estradiol, traditionally considered an ovarian hormone, is synthesized within the brain and affects local neuronal activity [1]. In zebra finches, hearing conspecific song induces estradiol release in the auditory forebrain, which rapidly alters firing properties both in that area and in downstream sensorimotor regions.…”
Section: Donna L Maneymentioning
confidence: 99%